Pre-clinical development of NOX2/ROS blood-based biomarker of TBI - Emediato, Isabella Dias (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
There is an urgent need to develop predictive biomarkers for traumatic brain injury (TBI) to aid clinical diagnosis and treatment of head injury patients. NADPH oxidase 2 (NOX2) activity and oxidized biomarkers are being evaluated as clinical biomarkers of neurodegenerative diseases. DHR123 is a reactive oxygen species (ROS) dye routinely used to diagnose chronic granulomatous disease (CGD), a genetic disorder characterised by defects in NOX2 activity. It can be used to measure ROS release in fresh whole blood using flow cytometry protocols. Previous studies from our lab used DHR123 to investigate systemic immune function following moderate-to-severe TBI in mice, and they revealed that TBI significantly increases leukocyte-derived ROS levels at day 3 post-injury. There appears to be a biphasic response to TBI because ROS levels in blood decrease below baseline at day 7 post-injury, before rebounding and becoming highly elevated at day 60 post-injury. DHR123 was also used to assess stimulus-induced respiratory burst activity (PMA/ionomycin challenged) in peripheral leukocytes after TBI. Under these conditions there was no change in burst potential in bone marrow-derived myeloid cells at day 3 post-injury. However, stimulus-induced ROS was significantly reduced by >50% in monocytes and neutrophils at day 60 post-injury. These data indicate that, upon stimulation, respiratory burst is impaired in peripheral myeloid cells at chronic time points after TBI. Based on these findings the goal of this project was to combine DHR123 and a NOX2 specific antibody to measure peripheral NOX2/ROS activity in leucocytes in the blood of sham and TBI mice during acute and chronic time points. We initially developed and optimized the NOX2/ROS assay in vitro using a human neutrophil-like cell line (HL-60) and had some successful results. We performed linear regression analyses between MFI DHR123 (ROS probe) and MFI NOX2 (gp91phox antibody) to assess the correlation between these two probes in different conditions (non-stimulated, stimulated, with NOX2 inhibitors) and successfully demonstrated a significant correlation that encouraged us to move forward in our project and apply this assay to experimental TBI studies in mice. We then examined ROS release and NOX2 activity/expression in baseline and stimulated states of neutrophils and monocytes from the blood of sham and TBI mice at different time points (1,7, and 14 days post-injury). Interestingly, we observed that upon stimulation at 14 days post-injury the peripheral immune system already shows signs of impairment, whereas previously this impairment was observed at 2 months post-injury. Blood neutrophils from injured mice did not respond as expected after PMA/ionomycin stimulation in both outputs: MFI DHR123 and MFI NOX2. Our preliminary results were promising and corroborated our hypothesis that after TBI the peripheral immune response becomes dysfunctional with time. These preliminary experiments demonstrate that the NOX2/DHR123 flow cytometry assay is easy to use and could potentially be translated to the clinical setting as a functional biomarker, to aid management and outcome prediction in TBI patients.
APPROVED
Keywords: TBI; NOX2; biomarker